Ketogenic diets are not beneficial for athletic performance: response to Noakes - Burke, L. M.; Whitfield, J. (Medicine & Science in Sports & Exercise, 2024)
We thank Professor Noakes for his insights on the contribution of hypoglycemia (or glycogen depletion) to exercise capacity (1). However, we feel that a holistic rather than reductionist approach is required to tackle the specific focus of this perspective: the effect of a ketogenic diet on athletic performance. We reiterate points from our original article (2): 1) that sports performance is explained by a complex interaction of factors, and 2) rather than claim a single truth to a superior dietary approach, sports scientists should identify nuances and context within the characteristics of the athlete and the event to determine the most suitable nutrition approach(es).